Virtual Anti-racism: Pleasure, Catharsis, and Hope in Mafia III and Watch Dogs 2. Issue 1 (February 2020) - Leonard, David J.
This essay examines the representation and consumption of Mafia III and Watch Dogs 2 as a site of catharsis, pleasure, and empowerment. Through not only its representation of white supremacy but its rendering of intervention and transformation as violence, Mafia III and Watch Dogs 2 offer a powerful inscription of gratification. In other words, offering both a space of oppositional gaze and a virtual reality invested in challenging gaze based in violence, Mafia III and Watch Dogs 2 reimagine the conventions of both video games and violence.